Upaya Guru Pendidikan Agama Islam dalam Mengatasi Kecanduan Scrolling Tiktok pada Siswa SMK Kamandaka Bogor - Dewi Nurkamila; Salati Asmahasanah; Noneng Siti Rosidah (Universitas Islam Negeri Alauddin Makassar, 2024)
The purpose of this study is to learn about the efforts of the islamic education teacher to overcome scrolling tiktok addiction to high school students Kamandaka Bogor and to find out what is a teacher's obstacle to overcoming scrolling tiktok addiction to students. The method of study that researchers use is a qualitative study method with a type of approach that leads to field study. As for the data-collection techniques that researchers use: observation, interview and documentation. This research shows that the attempts made by PAI teacher in the minimize and overcome scrolling tiktok addiction in Kamandaka Bogor which is to chide, to give direction, to give students views, Instilling learning and understanding about good characters and inserting counseling materials when in the classroom or when the learning materials take place and the last effort is to call the student specifically to take counseling counseling to the bk room so that the student can exert himself in wise and good use of his time. As for the obstacle that teacher PAI found in dealing with the scrolling addiction is the limited time of teachers and students in the school ward.